Hibriditas Budaya Jaran Kepang Turonggo Budoyo Sebagai Pelestarian Budaya Masyarakat Suku Tengger - Fatihah, Lauhil; Riyanto, Edi Dwi (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Jaran Kepang Turonggo Budoyo is one of the Jaran Kepang performing arts which was founded by the people of Sapikerep Village, Sukapura District, Probolinggo Regency as an effort to preserve the culture of the Tengger Tribe community. As the Tengger Tribe people who live in the Probolinggo Regency area, the geographical and socio-cultural conditions also influence the cultural color of the Tengger Tribe people who live in the area and produce various cultural hybridities, including in the field of culture. This research aims to determine the hybridity of the Jaran Kepang Turonggo Budoyo culture as a cultural preservation of the Tengger Tribe community. This research method uses field methods, namely case studies. Data collection techniques were carried out through interviews, observation and literature study. The analytical method used in this research is an interpretive qualitative method which is using a cultural studies analysis model. The results of this research are that the cultural hybridity that occurs in the Tengger Tribe community who live in Sapikerep Village, Sukapura District, Probolinggo Regency has influenced all aspects of the community's life. One of them is the cultural aspect in the field of performing arts, namely Jaran Kepang Turonggo Budoyo. The cultural hybridity that occurs in Jaran Kepang Turonggo Budoyo is a form of cultural preservation in the field of performing arts as an effort to maintain the preservation and resilience of the Tengger Tribe's culture.